Life history predicts flight muscle phenotype and function in birds. Issue 5 (26th March 2020) - DuBay, Shane G.; Wu, Yongjie; Scott, Graham R.; Qu, Yanhua; Liu, Qiao; Smith, Joel H.; Xin, Chao; Hart Reeve, Andrew; Juncheng, Chen; Meyer, Dylan; Wang, Jing; Johnson, Jacob; et al.
Abstract: Functional traits are the essential phenotypes that underlie an organism's life history and ecology. Although biologists have long recognized that intraspecific variation is consequential to an animals' ecology, studies of functional variation are often restricted to species‐level comparisons, ignoring critical variation within species. In birds, interspecific comparisons have been foundational in connecting flight muscle phenotypes to species‐level ecology, but intraspecific variation has remained largely unexplored. We asked how age‐ and sex‐dependent demands on flight muscle function are reconciled in birds. The flight muscle is an essential multifunctional organ, mediating a large range of functions associated with powered flight and thermoregulation. These functions must be balanced over an individual's lifetime. We leveraged within‐ and between‐species comparisons in a clade of small passerines ( Tarsiger bush‐robins) from the eastern edge of the Qinghai–Tibet Plateau. We integrated measurements of flight muscle physiology, morphology, behaviour, phenology and environmental data, analysing trait data within a context of three widespread, adaptive life‐history strategies—sexual dichromatism, age and sex‐structured migration, and delayed plumage maturation. This approach provides a framework of the selective forces that shape functional variation within and between species. We found more variation in flight muscle traits within species than has been previously described between species of birds under 20 g. This variation was associated with the discovery of mixed muscle fibre types (i.e. both fast glycolytic and fast oxidative fibres), which differ markedly in their physiological and functional attributes. This result is surprising given that the flight muscles of small birds are generally thought to contain only fast oxidative fibres, suggesting a novel ecological context for glycolytic muscle fibres in small birds. Within each species, flight muscle phenotypes varied by age and sex, reflecting the functional demands at different life‐history stages and the pressures that individuals face as a result of their multi‐class identity (i.e. species, age and sex). Our findings reveal new links between avian physiology, ecology, behaviour and life history, while demonstrating the importance of demographic‐dependent selection in shaping functional phenotypic variation. Abstract : The authors found more variation in avian flight muscle traits within species of Tarsiger bush‐robins than has been previously described between other species of small birds. This variation was associated with the discovery of mixed fibre types (glycolytic and oxidative) in the flight muscle of all three study taxa, suggesting a novel ecological context for glycolytic fibres in small birds.